The Analyzing Human Existence Through Fyodor Dostoevsky’s literary contributions - Nguyen, Quynh (Kalágatos, 2024)
This study examines the existentialist perspectives within the works of Fyodor Dostoevsky, a pivotal 19th-century Russian literary and philosophical figure. Dostoevsky is celebrated for introducing existential themes to Russian literature, with his narratives deeply rooted in the human condition. His key works, such as “Notes from Underground,” “Crime and Punishment,” “The Idiot,” and “The Brothers Karamazov,” delve into the human psyche challenged by the societal norms of 19th-century Russia. This paper seeks to dissect Dostoevsky’s nuanced examination of self-discovery, the pursuit of genuine existence, ongoing inner turmoil, solitude as a means to spiritual liberation, and the significant role of religious belief in shaping human experience. Through an analytical lens, this research scrutinizes the existential quandaries faced by Dostoevsky’s characters, positing that his literary and philosophical contributions not only shed light on human complexity but also serve as an enduring meditation on the nature of existence.